Effectiveness of Article 273 of Law No. 22 of 2009 concerning Traffic on Road Accidents (JURNAL HUKUM SEHASEN, 2020)
The mobility of people and goods with motorized vehicles is developing so fast as a result of increasing welfare and advances in transportation technology. This has an impact on the increasing frequency of traffic accidents with victims of drivers and road users. There are three main factors that cause accidents, the first is the human factor, the second is the vehicle factor and the last is the road factor. From this road factor, the author discusses the causes of traffic accidents, in Article 273 of Law Number 22 of 2009 concerning Road Traffic and Transportation regulates the Government's responsibility for accidents due to damaged roads. For the use of legal theory in research as an analytical tool for discussing legal events or facts proposed in the thesis research problem, the theory used is the theory of responsibility and the theory of law enforcement. The author uses empirical or sociological research methods. Factors constraining the Government in implementing Article 273 of Law No. 22 of 2009 concerning traffic are the absence of a Government Regulation that regulates in more detail those relating to Article 273. Regarding who is responsible for the operation of the road. This uncertainty can have an impact on the application of article 273 by law enforcement. People who do not report accidents caused by damaged roads or potholes. For various reasons there are those who do not know and there are those who do not want to deal with law enforcement officers, who consider accidents to be a disaster then the factors of law enforcement officials themselves and the laws made by the government are not implemented because they are related to government accountability.